Are healthcare professionals being left in the lurch?: the role of structural barriers and information resources to promote physical activity to cancer patients - Haussmann, Alexander; Ungar, Nadine; Gabrian, Martina; Tsiouris, Angeliki; Sieverding, Monika; Wiskemann, Joachim; Steindorf, Karen (Supportive care in cancer, 2018)
Purpose Although many cancer patients benefit from physical activity (PA), healthcare professionals (HCP) still do not promote it routinely. Including different groups of HCP, this study aimed to examine how structural barriers are perceived as impeding by HCP for promoting PA to cancer patients, how the perceptions of structural barriers are associated with promoting PA, and how HCP react to information resources. - Methods A total of 287 physicians in outpatient care, 242 physicians in inpatient care, and 388 oncology nurses completed our questionnaire (paper-pencil or online). Participants assessed nine different structural barriers (on a 4-point Likert Scale) and reported their PA promotion frequency. Further, they could request three different kinds of information resources about PA in oncological settings. - Results Across professional groups, more than 70% of HCP indicated that they promoted PA to their cancer patients often or routinely. Oncology nurses indicated that they were more impeded in promoting PA by six structural barriers than physicians (all p < .01). BNot enough time per patient^ and Black of an expert contact person^ were associated with a reduced PA promotion in two professional groups (all p < .05). Information resources were requested by 69.5% of the participants: mostly physicians working in outpatient care and especially by those perceiving structural barriers. - Conclusions Although a big proportion of HCP reported that they frequently promoted PA, our findings suggest that HCP still perceive structural barriers. The perception and influence of structural barriers differed between professional groups, pointing to the importance of profession specific guidance.
Gesehen am 22.10.2019